Improving the Effectiveness of Crude-Oil Hydrocarbon Biodegradation Employing Azotobacter chroococcum as Co-Inoculant - PUJAWATI SURYATMANA PARNADI; EDWAN KARDENA; ENNY RATNANINGSIH; . WISJNUPRAPTO (Microbiology Indonesia, 2007)
Azotobacter chroococcum has a great potential as biosurfactant producing bacteria and was used as co-inoculant to promote the rate of hydrocarbon biodegradation. The rate of hydrocarbon biodegradation were 0.01212, 0.01582, and 0.01766 per day for Acinetobacter sp., Bacillus cereus and the consorsium culture respectively. On the other hand, the rates of biodegradation using Azotobacter as co-inoculant were 0.1472, 0.01612, and 0.02709 g per day. Azotobacter chroococcum co-inoculant has the capability of increasing biodegradation efficiency of crude oilhydrocarbon. The biodegradation efficiency of petroleum hidrocarbon was increated by 13.4, 14.6, and 14.4% within the Petrobacter cultures.